An Investigation on Radiation Shielding Properties of Borosilicate Glass Systems - ŞEN BAYKAL, Duygu; TEKİN, Huseyin Ozan and ÇAKIRLI MUTLU, R. Burcu (International Journal of Computational and Experimental Science and Engineering, 2021)
The aim of this research is to examine the radiation shielding properties of 5B2O3-40SiO2-(55-x)Al2O3-xBaO (BSABa-x) glass systems, which are containing barium and aluminum oxide added to borosilicate glasses, with varying from 25 to 34 weight fractions. Shielding parameters, such as linear attenuation coefficients (LAC), mass attenuation coefficients (MAC), mean free path (MFP), effective atomic number (Zeff), effective electron density (Neff), half-value layer (HVL), tenth-value layer (TVL), effective atomic weight (Aeff), exposure buildup factors (EBF) and energy absorption buildup factors (EABF) enable us to obtain information about the radiation shielding power of composite glass material groups. Therefore, the mass attenuation coefficients (MAC), for the 0.015–15 MeV gamma-ray energies are obtained by using the Py-MLBUF online software to determine photon shielding parameters of BSABa-x glasses. The results are shown that the glass which contains higher BaO concentration has higher mass attenuation coefficients. BSABa-34 glass has the highest MACs, ranging from 0.111 cm2/g to 90.400 cm2/g, while BSABa-25 glass has the lowest values, ranging from 0.099 cm2/g to 69.000 cm2/g. The BSABa-34 glass with the highest BaO contribution has the thinnest MFP and HVL values. In addition, photon buildup is minimized by adding BaO to the BSABa-x glasses. Accordingly, we can conclude that adding BaO to aluminum borosilicate glasses at increasing rates, improves nuclear radiation resistance properties.